Relationship between the Development of Outer Hair Cell Electromotility and Efferent Innervation: A Study in Cultured Organ of Corti of Neonatal Gerbils - He, David Z. Z. (J Neurosci, 1997)
Outer hair cell (OHC) electromotility, which powers the cochlear amplifier, develops at a later stage of hearing ontogeny. There has been speculation whether efferents play a necessary role in directing or achieving OHC maturation in mammals. In this study, we examine whether the development of OHC motility depends on the establishment of efferent innervation of the cells’ synaptic pole by measuring electromotility of OHCs grown in cultures, deprived of efferent innervation. Tissue cultures of the organ of Corti were prepared from the cochleas of newborn gerbils. Solitary OHCs were obtained from 4- to 15-d-old cultures by enzymatic digestion and mechanical trituration. Length changes evoked by transcellular electrical stimulation were detected and measured with a photodiode sensor. Results show that OHCs develop electromotility between 6 and 13 d in culture without the presence of efferent innervation. The timetable for the onset of OHC electromotility is comparable with that in vivo. This demonstrates that the ontogeny of OHC electromotility is an intrinsic process that does not require the influence of efferent innervation.